Bottle gourd (lagenaria siceraria) extracts improve glucose and lipid metabolism in 3T3-L1 adipocytes - Sassi, Assia; Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher (MATTIOLI 1885, 2019)
The aim of this study was to investigate the effect of bottle gourd which belong to family of cucurbitaceae (Lagenaria Siceraria (LS) on hyperglycemia by assessing the cells viability, adipogenesis, adipolysis, glucose uptake, adiponectin and leptin using 3T3-L1 adipocytes as a model. Fresh bottle gourd were washed thoroughly with distilled water and segregated into three parts i.e. whole vegetable (LSW), peels (LSP) and seeds (LSS) and were separately blended with water and ethanol. Thus obtained six types of extracts i.e. three for water whole vegetable (LSWw), peels (LSPw), seeds (LSSw) and three for ethanol whole vegetable (LSWe), peels (LSPe) and seeds (LSSe). The 3T3-L1 adipocytes were treated with these extracts for cells viability, adipogenesis, adipolysis, glucose uptake, adiponectin and leptin. The collected data was compiled and statistical analysis were performed. Mainly, one-way analysis of variance (ANOVA) were performed followed by Tukey’s post-hoc test to ascertain differences in the means. The lipid droplet formation was significantly (P<0.001) higher in the adipocytes treated with the extracts of LSWw, LSSw, LSWe, LSWe, LSSe and lower in the extracts of LS peels (LSPw, LSPe) compared to induction medium (MDI)/insulin (control). The extracts also significantly (P<0.001) increased glycerol release during adipolysis compared to the control. It caused a significant (P<0.001) increase in adiponectin concentrations for LSPw, LSWw and a decrease in leptin concentrations for the water extracts of the LSPw. The present study showed that there was hypoglycaemic effect of LS extract by improving the regulation of adipogenesis, adipolysis, glucose uptake, adiponectin and leptin in the adipocytes mainly due to the seeds.